Peran Intelijen terhadap Permasalahan Orang Asing di Provinsi Sulawesi Selatan: Studi Kasus Penegakan Hukum - Hendrik F. Siregar; Sayid Ali Zainal Abidin Assegaf (Al-Ishlah: Jurnal Ilmiah Hukum, 2022)
This study aims to examine and analyze the effectiveness of the Role of Intelligence and the factors influencing law enforcement against foreigner problems in South Sulawesi Province. This research uses empirical legal research methods. The primary data collection was carried out using a questionnaire, while the secondary data was collected using literature study techniques. The data obtained in this research is quantified using a quantitative descriptive analysis model, then described using a frequency distribution table for answer research purposes. The results show that the role of Intelligence in law enforcement against foreign problems consists of administrative control and field surveillance. The implementation of these two roles has been less effective in South Sulawesi Province. As for what influences the role of Intelligence in law enforcement against foreigner problems, it consists of three dominant factors: legal factor, law enforcer factor, and cultural factor. These three factors are less influential in supporting Intelligence’s role. This condition simultaneously answers the problem regarding the role of Intelligence which is less effective against foreign problems in South Sulawesi Province. Therefore, it is recommended for the Ministry of Law and Human Rights strengthen the Foreign National Oversight Team’s position based on the MoLHR Regulation. In addition, the Ministry must provide an adequate budget allocation to the Foreign National Oversight Team regarding the need to provide complete facilities to support the role of field surveillance. Furthermore, Intelligence personnel in the Foreign National Oversight Team must ensure that information is up to date so that it can make strategic decisions and policies. Thus, the effectiveness of the role of Intelligence in law enforcement against foreigner problems in South Sulawesi Province can be realized in the future.